PENGARUH MEREK DAN DISTRIBUSI TERHADAP LOYALITAS PELANGGAN PADA PT. CENTRAL BEARINDO INTERNATIONAL MEDAN - BAMBANG SUTEJO (LP2MTBM MAKARIOZ, 2020)
This study aims to determine how much influence of Brand and Distribution of Customer Loyalty at PT. Central BearindoInternational Medan. The research methodology used is quantitative descriptive method, the unit of analysis in this researchis PT. Central Bearindo International and its observation units are customers at PT. Central Bearindo International.Population in this research is customer at PT. Central Bearindo International totaling 55 customers. The technique ofdetermining the number of samples used in this study is a sampling technique saturated and totaling as many as 55customers. The research method used is the technique of data collection through library research and field researchconducted systematically based on research objectives. The method of analysis used to solve the problem and prove thehypothesis is by descriptive analysis, regression analysis. This analysis includes: validity and realiability, classic assumptiontest, multiple regression analysis, hypothesis testing through t and F test, and test of coefficient of determination (R2).From the analysis obtained regression analysis Customer Loyalty = 2,536 + 1,143 Brand - 0,026 Distribution + e The resultof determination coefficient test (R2) shows that 90,4% Customer Loyalty variable influenced by Brand and Distributionvariables, while the rest equal to 9,6% other factors or variables outside of models such as advertising, price, and others notaddressed in this study. F test results show that Fcount> Ftable is 245,609> 3.18 which means independent variables (Brandand Distribution) simultaneously affect the dependent variable (Customer Loyalty). While t test indicate that Brand variablehave positive and significant influence to Customer Loyalty at PT. Central Bearindo International where tcount 19,458> ttable1.674 and Distribution variable has no effect and not significant to Customer Loyalty at PT. Central Bearindo Internationalwhere tcount -0,367 < ttable 1.674.